2004
DOI: 10.1007/s00595-003-2703-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Non-Hodgkin?s Lymphoma in a Patient with Chronic Hepatitis C: Report of a Case

Abstract: We report a case of primary hepatic non-Hodgkin's lymphoma in a 77-year-old man with chronic hepatitis C. Laboratory data revealed slightly elevated liver function parameters and positive antibody for hepatitis C virus (HCV). Abdominal ultrasonography showed a low-echogenic tumor, about 5 cm in diameter, in the left lateral segment. Abdominal computed tomography showed that the tumor was marginally enhanced in the early phase, but no enhancement was seen in the late phase. Magnetic resonance imaging showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Due to the small number of reported cases, the viability of the optimal treatment for patients with PHL is still debated. Although we believe that chemotherapy is essential after a pathological diagnosis to avoid oversurgery [2], surgery followed by adjuvant chemotherapy is one of the treatment options for patients with localized disease, as carried out in our present case [2,12,18].…”
Section: Discussionmentioning
confidence: 87%
“…Due to the small number of reported cases, the viability of the optimal treatment for patients with PHL is still debated. Although we believe that chemotherapy is essential after a pathological diagnosis to avoid oversurgery [2], surgery followed by adjuvant chemotherapy is one of the treatment options for patients with localized disease, as carried out in our present case [2,12,18].…”
Section: Discussionmentioning
confidence: 87%
“…Only one of the three patients was immune-suppressed, and none presented with signs of chronic hepatopathy. Association of primary hepatic lymphoma with cirrhosis and chronic hepatitis has been described in 30% of cases (12)(13)(14)(15) . Although the reason for this association still remains unclear, the diagnosis of NHL should be considered in cirrhotic patients with voluminous hepatic mass and normal alphafetoprotein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Primary non-Hodgkin's lymphoma of the liver is rare, although the number of reported cases in hepatitis C virus (HCV)-infected individuals is increasing [5], with large B-cell lymphoma the usual histologic type. A recent meta-analysis revealed that HCV prevalence in patients with non-Hodgkin's lymphoma was 15%, as opposed to 1.5% in the general population and 2.9% in patients with other hematologic malignancies, implying a causative role of HCV in non-Hodgkin's lymphoma [6].…”
Section: Commentarymentioning
confidence: 99%